452 Poor team training is a PETT hate for many: paediatric emergency team training: a virtual course to enhance real life team work. (17th August 2022) - Berg, Richard; Hall-Jackson, Megan; Hoyle, Jessica; Murray, Fiona; Anpananthar, Amutha
Abstract : Aims: Multidisciplinary teams work together, under significant stress, towards time critical common goals of stabilising critically ill children. These teams often assemble only when needed which may contribute to ineffective teamwork, and therefore error. For example, a paediatrician in a district general hospital may only interact with an operating department practitioner when a child is critically unwell; a team of experts does not necessarily ensure an expert team. However, efficient communication and teamwork is crucial for teams to function effectively. Team training has long been used in military and aviation sectors to enhance team working skills. More recently, courses have been developed in healthcare to enhance team working skills. Due to the Covid-19 pandemic, it was not possible to deliver these courses in the same way and our previous course, SPARTACUS (Simulated Paediatric and Anaesthetic Response to Assist Children's Urgent Stabilisation) did not suit the online environment. We designed a denovo course, Paediatric Emergency Team Training (PETT) course with the aims of improving teamworking skills and increasing participant confidence in their role in the team. Methods: The PETT course, delivered on Microsoft Teams, is modelled on the TeamSTEPPS model of effective teamwork. This incorporates 4 domains; communication, leadership, mutual support and situation monitoring. Small groups (maximum 8 participants with 3 faculty) allowed a more intimate environment to be created. The medical participants were all experienced, middle grade or above to focus the learning on teamworking skills rather than medical knowledge. Ground rules were established, including having cameras on whenever possible. Varied pedagogical modalities were used to enhance the learning experience, including gamification with breakout room games to highlight communication and team strategy. Interactive workshops were used to discuss contributing factors and the dynamics of effective teamwork, barriers to effective teamwork, and strategies to enhance teamwork using pre-recorded video scenarios of acutely unwell children to debrief with the online participants. The course was evaluated via surveys before, immediately after and 8 weeks after the course. Results: PETT has been delivered so far to 20 participants, with one pilot and two full courses. Participants have come from paediatric backgrounds (paediatric registrars), anaesthetic backgrounds (consultants and registrars), nursing backgrounds and operating department practitioners. In pre-course surveys, 41% of participants (5/12) agreed with the statement 'when teamwork within a multidisciplinary team, or across specialties is challenging, I have tools to help.' After the course, 91% (10/11) agreed with this statement. Before PETT, 41% of participants (5/12) agreed that 'communication skills can be taught effectively online', whereas after the course 91% (10/11) agreed with this statement. Before PETT, 66% of participants (8/23) felt confident in 'communicating with other members of the multidisciplinary team, and with other specialties' whereas afterwards, 91% (10/11) felt confident in doing this. Conclusion: We have demonstrated that PETT course, as an online course for the multidisciplinary team (aiming at senior level), has met our aims of a course to improve teamwork and team confidence. Going forward, we intend to deliver this biannually in addition to our previous face-to-face courses such as SPARTACUS.